The efficiency of banks and stock performance: Evidence from Saudi Arabia - Mohammad Alsharif (Cogent Economics & Finance, 2021)
The aim of this study is to extend the literature by extensively investigating the efficiency of banks in Saudi Arabia and examining its relationship with stock performance through relying on six measures of efficiency (three price efficiencies and three technical efficiencies). This study employs the data envelopment analysis (DEA) on all listed Saudi commercial banks over the period 2006-2018 ensuring the robustness of the results, and the multiple-regression analysis method is used to empirically test the impact of the efficiency changes on bank stock returns. The results indicate that Saudi banks are more technically efficient, and their price efficiencies are more volatile. Furthermore, changes in bank efficiency are positively related to stock performance; however, these positive relationships are only statistically significant with the changes in profit and scale efficiency measures implying that investors pay much attention to the improvement in bank profitability and future dividends.
Keywords: 330; Bank efficiency; DEA; Price efficiency; Saudi Arabia; Stock performance; Technical efficiency